Living donor liver transplantation for Budd–Chiari syndrome: Overcoming a troublesome situation. Issue 43 (October 2016) - Ara, Cengiz; Akbulut, Sami; Ince, Volkan; Karakas, Serdar; Baskiran, Adil; Yilmaz, Sezai
Abstract: Background: The aim of the study was to report the detailed surgical techniques of living donor liver transplantation (LDLT) in patients with Budd–Chiari syndrome (BCS). Methods: Demographic and surgical techniques characteristics of 39 patients with BCS who underwent LDLT were retrospectively reviewed. Thirty-two of them had native vena cava inferior (VCI) preservation and 6 had retrohepatic VCI resection with venous continuity established by cryopreserved VCI (n = 4) or aortic graft (n = 2). In 1 patient, the anastomosis was established between the graft hepatic vein (HV) and the suprahepatic VCI. For preservation of the native VCI, immediately before the graft implantation, the thickened anterior, and right/left lateral walls of the recipient VCI were resected caudally and cranially until the intact vein wall was reached, and then an anastomosis was created between the (HV) of the graft reconstructed as a circumferential fence and the reconstructed recipient VCI. For resection of the retrohepatic VCI, the anastomosis was created with the same technique in all 6 patients in whom VCI was reformed by using a vascular graft. Results: Post-LT complications developed in 19 of the patients. Complications related to the biliary anastomosis accounted for 12 of these cases, with 11 treated by PTC and/or ERCP, and 1 by hepaticojejunostomy. Two of the 39 patients developed recurrent BCS and were treated by interventional radiological methods. Thirteen patients died and none were related to the BCS recurrence. Conclusion: Favorable outcomes are achievable with LDLT treatment of patients with BCS, which carries important implications for countries with inadequate cadaveric donor pools.